APPLICATION OF GOOGLE SHEETS AND MICROSOFT EXCEL INTEGRATION FOR LEARNING EVALUATION - Fuad Nasir (Cirebon International Conference on Education and Economics Proceeding, 2024)
In this digitalized era, the landscape of learning evaluation has experienced a profound evolution thanks to the integration of technology-driven tools. Among these, Google Sheets and Microsoft Excel stand out as pivotal platforms within educational settings, facilitating the management and in-depth analysis of learning data. This study aimed to explore a prototype integration of Google Sheet and Microsoft Excel in increasing the effectiveness of learning evaluation. The research focused on developing a learning evaluation system that seamlessly integrates these two tools. This approach has demonstrated its efficacy in expediting the analysis of learning evaluation data compared to traditional methods. By harnessing spreadsheet technologies like Google Sheets and Excel, educators have revolutionized how they collect, interpret, and present insights from student learning experiences. Google Sheets excels in its accessibility and capability for real-time collaboration among educators, making it ideal for dynamic classroom environments. On the other hand, Excel offers robust analytical functionalities, enabling educators to delve deeper into data patterns and trends. Together, these tools empower educators to conduct evaluations more efficiently, accurately, and collaboratively than ever before. Moving forward, it is encouraged that educators explore and exploit the full potential of these technologies to enrich their evaluation practices. By doing so, they can foster enhanced learning experiences tailored to the needs and progress of each student. Ultimately, the integration of Google Sheets and Microsoft Excel not only streamlines administrative tasks but also empowers educators to make data-driven decisions that positively impact educational outcomes.